Non-graft stent for the treatment of women with aorta coarctation - Yasseen Abdulruda Yasseen,; Karar Nadhm Obaid Aljabry,; Ammar Jabbar Majeed,; Saif M. Hassan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Aortic Coarctation is one of the common congenital heart diseases.It is ranks sixth in frequency of congenital heart disease. It is a narrowing of aorta mostly in the region of the ligamentum arteriosum.Correction of coarctation of aorta is indicated in patient with symptom related to stenosis and hypertension related to coarctation, also when pressure gradient more than 20 mmHg and significant difference of blood pressure between upper limb and lower limb more than 20 mmHg.The operation was effective in all women without any immediate serious problems. Follow-up results indicated sustained improvement in pressure gradients and considerable therapeutic effects. Modest complications included local hematoma at the access site in 3 women, which resolved with conservative care. There are no occurrences of stent migration, aneurysm development, or re-stenosis were detected during the follow-up period. These data demonstrate that stent implantation for aortic coarctation is a safe and effective treatment option, producing persistent hemodynamic and clinical benefits.After one month following the procedure, there was no significant increase in blood pressure. Most patients achieved controlled blood pressure, with 22 women maintaining control without medication, 14 women requiring a single antihypertensive medication, and the remaining 4 women needing two or more antihypertensive drugs.